Exploring farmers’ decision-making : A systematic review of socio-economic, behavioral and technological influences - Poonthalir, Veeran; Muhammad Asraf, Abdullah; Nivakan, Sritharan (MARDI, 2024)
This systematic literature review examines the factors that influence farmer decision-making in agricultural practices, focusing on socio-economic, behavioral, and technological determinants. The review analyses 59 selected articles, identified through a rigorous process of identification, screening, eligibility and inclusion. It explores the key drivers of sustainable practice adoption, including economic incentives, social networks, cognitive traits and environmental challenges. The findings emphasise the critical roles of economic stability, resource availability, peer influence and adaptive strategies in technology adoption and climate resilience. The review also identifies gaps in current research, particularly the lack of longitudinal studies that assess the long-term impact of these factors. It encourages future research to use mixed methods approaches to gain a more comprehensive understanding of how these influences evolve. This review offers valuable insights for policymakers, researchers and practitioners seeking to support sustainable agricultural development.